SKRINING FITOKIMIA, UJI AKTIVITAS ANTIMIKROBA DAN ANTITUMOR TUMBUHAN OBAT KABUPATEN MANOKWARI - Bimo B. Santoso (FMIPA Universitas Papua, 2007)
Pythochemistry screening and testing of antimicrobial and antitumor activities was carried out on 31 species of medicinal plants distributed around Manokwari Regency. All parts of the plants were collected and screened for the presence of alkaloids, saponins, and tannins; antimicrobial and antitumor activity. The number of positive tests obtained are 17 (55, 3%) for alkaloids, 6 (19, 4%) for saponins, and 26 (84, 7%) for tannins. Eleven species shown inhibition activities (antimicrobial) to Candida albicans, Staphyloccocus aureus, and Echericia colii while only seven species have antitumor activity, especially against tumor cell P-388.